Iron Dynamics Shape Host-Pathogen Interactions - Brooke, Grant M.; Carter, Christopher A.; Dasgupta, Debolina; Gawhale, Snehal G.; Hayes, David T.; Jonak, Carissa M.; Joshi, Prabhu R.; Michel, Kristin; Pandey, Ashmita; Platt, Thomas G.; Tripathi, Aprajita (My University, 2023)
Hosts and their pathogens often compete for trace metal elements that are essential to each of their survival. Iron is one of these trace metal elements and consequently, iron dynamics are central in host-pathogen interactions. Here we review how competition for iron during infection influences host-pathogen interactions and shapes disease outcomes. Hosts have developed diverse mechanisms to limit nutrient availability to the pathogen, also known as nutritional immunity. In response to infection, vertebrate, invertebrate, and plant hosts generate a hypoferremic environment using a variety of iron-binding proteins and chelators, alongside iron transporters, to limit pathogen replication. To counter nutritional immunity responses, pathogens use TonB-dependent (e.g., siderophores) and TonB-independent mechanisms to scavenge ferric and ferrous iron. Pathogens also compete with the host-associated microbiota to access iron. Competition between microbes for iron can either hinder or facilitate pathogen establishment and proliferation within hosts. Iron dynamics are an exciting new avenue for therapeutic interventions that may be employed against a broad range of pathogens.